Peningkatan Hasil Belajar Siswa SMAN 2 Palembang melalui Model Discovery Learning pada Materi Trigonometri - Dinna Cilvia Asri; Sangkot Samosir (ARITHMETIC: Academic Journal of Math, 2020)
The research conducted was classroom action research to improve the learning outcomes of students of class XI MIPA 6 Senior High School 2 Palembang. Improved learning outcomes are carried out by using the discovery learning model during the learning process. As for this research, using a subject consisting of 35 students. The subject used by researchers in this study is the formula of the sum and difference of sine, cosine, and tangent of two angles. In the first cycle consisted of 3 meetings and Cycle II consisted of 2 meetings. This study uses instruments in the form of test results of learning and observation. Tests of learning outcomes are used by researchers as a way to find out the achievements of students from each cycle and observations are used by researchers to collect data during the learning process takes place. Quantitative and descriptive data analysis was used in this study. Based on the results of the study, it was found that the average value of students of class XI MIPA 6 on the first cycle test was 63.00 and increased on the second cycle test to 83.69. The results of this study indicate that learning using the discovery learning model can improve students' mathematics learning outcomes, i.e. 74.28%  of students have achieved indicators of success in the second cycle of research.